1998
DOI: 10.1021/jp980134n
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Molybdenum Species in Silica-Supported Molybdenum Oxide and Alkali-Ion-Modified Silica-Supported Molybdenum Oxide

Abstract: Silica-supported molybdenum oxide (MoO3/SiO2) and alkali-ion-modified MoO3/SiO2 samples were characterized by Mo K-edge XAFS and Raman spectroscopies. The structure of the molybdenum species in MoO3/SiO2 was confirmed to be monomeric and tetrahedral, (OMoO)O2. In alkali-ion-modified MoO3/SiO2, the structure of the molybdenum species varied with the kinds and/or the amounts of added alkali ions. In Na+-modified MoO3/SiO2 with sodium ions of the molar ratio Na/Mo < 1.0, the molybdenum species were mainly Na2Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 31 publications
9
66
0
Order By: Relevance
“…This feature has been assigned to the 1s-4d transition, and the intensity is considered to be proportional to the number of Mo@O double bonds per molybdenum atom (e.g., Cramer et al, 1978;Yokoi et al, 1987). Takenaka et al (1998) also used intensity and integrated area of this pre-edge feature to estimate the asymmetry of the species. The tetrahedral moiety [MoO 4 ] 2À in Na 2 MoO 4(s) displays a more intense pre-edge than MoO 3(s) , which has a distorted octahedral [MoO 6 ] structure (Takenaka et al, 1998;Leisegang et al, 2005; Table 2).…”
Section: Xanes Spectra Of Mo Solid Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature has been assigned to the 1s-4d transition, and the intensity is considered to be proportional to the number of Mo@O double bonds per molybdenum atom (e.g., Cramer et al, 1978;Yokoi et al, 1987). Takenaka et al (1998) also used intensity and integrated area of this pre-edge feature to estimate the asymmetry of the species. The tetrahedral moiety [MoO 4 ] 2À in Na 2 MoO 4(s) displays a more intense pre-edge than MoO 3(s) , which has a distorted octahedral [MoO 6 ] structure (Takenaka et al, 1998;Leisegang et al, 2005; Table 2).…”
Section: Xanes Spectra Of Mo Solid Compoundsmentioning
confidence: 99%
“…Takenaka et al (1998) also used intensity and integrated area of this pre-edge feature to estimate the asymmetry of the species. The tetrahedral moiety [MoO 4 ] 2À in Na 2 MoO 4(s) displays a more intense pre-edge than MoO 3(s) , which has a distorted octahedral [MoO 6 ] structure (Takenaka et al, 1998;Leisegang et al, 2005; Table 2). Such a distorted octahedral structure is typical of Mo(VI) compounds containing Mo in octahedral coordination; usually, Mo is bonded to 2 oxygen atoms at short distance ($1.60 Å ), 2 at intermediate distance, and 2 at a long distance ($2.3-2.4 Å ; Table 2).…”
Section: Xanes Spectra Of Mo Solid Compoundsmentioning
confidence: 99%
“…-, Mo 6? -oxide) containing silica-based materials such as zeolites and mesoporous silicas show the unique properties as efficient catalysts for various photocatalytic reactions, i.e., the decomposition of NO x , partial oxidation of hydrocarbons as well as reduction of CO 2 with H 2 O [1][2][3][4][5][6]. The transition metal oxide in these catalysts is considered to be highly dispersed state at the atomic level and exist in the well-defined structure on these surfaces or within the frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that supported Mo 6+ -oxide catalysts exhibit unique and high photocatalytic activity for various significant reactions such as the decomposition of NO in the presence of reductant gasses such as CO [1][2][3][4] or hydrocarbons [5], the partial oxidation of hydrocarbons into oxygen-containing compounds [6,7] and olefin metathesis [8][9][10][11]. It has, thus far, been revealed that the charge transfer excited triplet state of the highly dispersed tetrahedral Mo 6+ -oxide species plays a significant role in these photocatalytic reactions [12,13].…”
Section: Introductionmentioning
confidence: 99%